"What Kind of Place Do We Want to Live In?" Place, the Humanities, and Public Policy in Maine - Toner, Carol (Maine Policy Review, 2015)
Carol Toner explores the intersection of the humanities, public policy making, and quality of place. In 2014, a local protest against the site of a potential new landfill in rural Maine demonstrates how citizens can draw from their history and culture when considering public policy and quality of place. In this case, the humanities informed the making of public policy to benefit the greater good. Maine enjoys a participatory public policy process that depends on informed public input. The humanities, especially history, literature, and philosophy, help prepare citizens for this important role by teaching critical thinking, imagination, and compassion. Maine Studies students, through interdisciplinary and community-engaged research methods, draw from the humanities to examine public policy and to consider what is best for Maine people and their place.